Prospective Controlled Study of Gastroesophageal Reflux in Dogs with Naturally Occurring Laryngeal Paralysis. Issue 7 (9th September 2016) - Tarvin, Kiki M.; Twedt, David C.; Monnet, Eric
Abstract : Objective: To determine the frequency, nature, and magnitude of gastroesophageal reflux (GER) in dogs with laryngeal paralysis (LP). Study Design: Prospective comparative clinical study. Animals: Client‐owned dogs with LP and healthy client‐owned dogs (n = 6 each). Methods: Dogs underwent sedated laryngeal examination for diagnosis and grading of bilateral LP and for placement of a nasoesophageal dual pH/impedance probe. Endoscopy was used to confirm probe location and evaluate the distal esophagus. Data were recorded continuously. GER was defined as pH<4 or >7.5 lasting >2 seconds reaching a magnitude of 2 impedance sensors proximally. Results: The median total number of GER events per hour was 0.64 (range, 0.44–1.6) for the LP group and 0.53 (range, 0.38–1.0) for the control group ( P = 0.259; power = 0.50). The median total number of alkaline regurgitation events per hour was 0.37 (range, 0.17–0.93) for the LP group and 0.46 (range, 0.25–1.0) for control group ( P = 0.575; power = 0.57). The median total number of acidic regurgitation events per hour was 0.22 (range, 0–0.70) and 0.0 (range, 0–0.14) for the LP and control groups, respectively ( P = 0.025). Acidic reflux events reached the proximal pH sensor in 2 dogs in the LP group for a total of 4 reflux events and in 1 dog in the control group for a total of 3 reflux events ( P = 0.673). Conclusion: Based on the limited number of dogs studied, it appears that dogs with naturally occurring LP have increased acidic reflux events compared to clinically normal dogs. GER can reach the most proximal part of the esophagus.